Fuzzy PID Speed Control of Two Phase Ultrasonic Motor - Ma Qiujie; Shi Jingzhuo (Institute of Advanced Engineering and Science, 2014)
Because of ultrasonicmotor’s time-variable nonlinearity, a online adaptive correction of PID controlparameters based on fuzzy logic is presented. The special nature of ultrasonicmotor’s speed control are fully taken into account in designing fuzzy rules.The amplitude of driving voltage is used as the control parameter to realizethe control method. The experiments indicate that the control characteristicsare much better than that of PID controller.